Validation of an LC–MS/MS method for the simultaneous quantification of dabigatran, rivaroxaban and apixaban in human plasma. (February 2016) - Baldelli, Sara; Cattaneo, Dario; Pignatelli, Pasquale; Perrone, Valentina; Pastori, Daniele; Radice, Sonia; Violi, Francesco; Clementi, Emilio
Aim: Novel oral anticoagulants are characterized by a wide therapeutic window, yet the determination of their plasma–drug concentrations may be useful in some clinical conditions.Results: An LC–MS/MS method for the analysis of dabigatran, apixaban and rivaroxaban in human plasma has been successfully developed and validated. The analysis of plasma samples from patients given other concomitant drugs revealed no significant interference. By reanalysis of samples from patients on anticoagulant therapy, we found the percentage difference in results between the concentration of repeat and the original sample to be within the threshold limit of 20% in 60 of 63 specimens.Conclusion: The developed LC–MS/MS assay is easily applicable in the clinical management of patients on anticoagulation therapy.